Study of some immunological effects of methotrexate in people with rheumatoid arthritis - Faten kareem; Wijdan Thamer (Al-Qadisiyah Journal of Pure Science, 2019)
The aim of this study was to determine the effect of rheumatoid arthritis on some immunological criteria in women withrheumatoid arthritis at Marjan Specialist Hospital in Babil governate for the period from 20/10/2018 until 20/4/2019, when 90 samples of women agedbetween 25 to 55 years old into three groups: the first (30) women with rheumatoid arthritis Calming treatments. And the second(30) of women with rheumatoid arthritis who received methotrexate treatment. The third sample (30) included a sample of nonRA patients representing control.5 mL of venous blood was withdrawn and placed in a test tube and then placed in a centrifuge to separate the serum and performimmunological tests (Inter Lockin 4, Inter Lockin 6)Results showed a significant increase of P <0.0.5 in the level of interleukin (4.6) in infected women compared to the controlgroup.We conclude from the study that the incidence of rheumatoid arthritis had a significant effect on the level of interleukins (6.4) inwomen, and was the highest difference in the group of women who use analgesics as a treatment.The study showed that MTX had a significant effect in reducing measured parameter levels compared to control group